MASASE DAN PRESTASI ATLET - lntan Arovah, Novita (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2010)
Massage is one of the physiotherapy modalities that used by many athlete to improve the physical performance or to overcome the injury and other physical disruption of high intensity of physical working. To meet those aims, massage in a competition is done before the competition (preevent), in a competition (intra event) and after competition (post-event). This article are aim to cover the physiologic massage effect, the purposeÂ of the use of massage in a competition and the manipulation massage technique to overcome those purposes. Athlete, coach and massager have to understand that things because the use of right massages technique can give contributions in the effort of the improvement of athlete achievement.Â Keywords: massage, athlete achievement